PENGELOLAAN SAMPAH MENUJU DESA SEHAT DI DESA NGALANG, GEDANGSARI, GUNUNGKIDUL - Surahma Asti Mulasari; Sulistyawati Sulistyawati; Tri Wahyuni Sukesi; Fatwa Tentama (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2019)
Healthy villages are the realization of caring, responsive, and ability of rural communities to recognize, prevent, and overcome health problems independently. To help achieve the Ngalang village program and build the independence of Ngalang Village, it was done by a synergy among community and university. The primary goal was empowered communities to create jobs to reduce unemployment. We occupied counselling and training on the dangers of garbage, processing waste through a waste bank, also visiting a garbage bank, namely the K3S Jatikuning waste bank. The impact from this activity was the increase of knowledge and skills of the community about how processing the garbage to have economic value and increasing community empowerment to create a tourism village.